Effect of mycorrhizal fungi in combination with botanicals, fungicides and bio-agents in ameliorating Fusarium wilt management in chickpea (Cicer arietinum) - KHANNA, ANNIE; RAJ, KUSHAL; KUMAR, PANKAJ (The Indian Journal of Agricultural Sciences, 2021)
Fusarium wilt incited by Fusarium oxysporum f. sp. ciceris causes substantial economic losses in chickpea. Tostudy the effect of mycorrhizal inoculation in combination with different bio-agents, fungicides and botanicals onthe Fusarium wilt incidence and yield of chickpea, field trials were conducted during 2019–20 at the research field ofCCS Haryana Agricultural University, Hisar. Mycorrhizal fungi were found to be beneficial in alleviating chickpeawilt incidence and upsurging the yield components of chickpea. The mycorrhizal fungus Glomus mosseae performed better than Glomus hoi, evincing the importance of mycorrhizal species. Seed soaking provided more disease control in comparison to soil drenching of plant extracts, bio-agents and fungicides except azoxystrobin 23% SC in variety JG 62 in which mode of application of fungicide had no significant effect on disease incidence. Amongst mycorrhiza × treatment interaction, carbendazim 50% WP provided utmost disease control (>80%) in the soil pre-inoculated with G. mosseae and Glomus hoi, followed by azoxystrobin 23% SC and Trichoderma viride, while aqueous extract of datura leaves was the least effective in both chickpea varieties JG 62 and C 235.